Digital Learning: How the Process Enhances Students’ Digital Literacy - Adelia Alfama Zamista; Khairul Azmi (Jurnal Penelitian Pendidikan IPA, 2023)
Information and Communication Technology (ICT) is now frequently applied in education. This makes the learning process one of the activities that can empower digital literacy. The research aims to explore information about students' digital literacy levels based on their self-assessment and how the learning process can train the indicators on digital literacy to students. This research was conducted using a qualitative descriptive approach. Using a purposive sampling technique, the sample for this research was 38 Tadris IPA students who had participated in lecture activities with digital learning substitution. The research instrument is a digital literacy level self-assessment questionnaire which refers to a global framework of reference on digital literacy skills which consists of 4 digital literacy sub-indices. The results showed that Tadris Physics students had a digital literacy index in the good category. This is supported by the implementation of lectures that provide opportunities for students to empower their digital literacy, such as the implementation of digital technology-based learning (use of LMS or blended learning), and an assignment system that requires students to think critically while searching for information independently through various digital platforms.